Pengaruh Kepemilikan Institusional, Struktur Modal, dan Pengungkapan Sustainability Report Terhadap Nilai Perusahaan - Maharani Nadia Nariswari; Rakendro Wijayanto; Marieta Ariani (Economic Reviews Journal, 2025)
This study aims to examine the influence of institutional ownership, capital structure, and sustainability report disclosure on firm value (empirical study of energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023). The population of this study consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2021 to 2023. The sampling technique used is purposive sampling, based on specific criteria. These criteria include energy sector companies listed on the Indonesia Stock Exchange from 2021 to 2023, companies that published annual reports from 2021 to 2023, companies that published financial statements from 2021 to 2023, and companies that issued sustainability reports aligned with GRI standards from 2021 to 2023. The data were obtained from the companies official websites and www.idx.co.id. The expected results in this study are concluded as follows First, there is an effect of institutional ownership on firm value. Second, there is no effect of capital structure on firm value. Third, there is an influence of sustainability report disclosure on firm value. Apart from this research, companies are expected to be responsible to stakeholders in order to run their operations sustainably and optimally. This responsibility includes aspects that can be measured financially, such as profits earned and responsibilities in managing economic, social and environmental aspects